PENGARUH PENGALAMAN PRAKTIK KERJA INDUSTRI TERHADAP KESIAPAN KERJA PESERTA DIDIK DI SMK NEGERI 2 BANDUNG - Ramadhan, Gilang; Kusuma, Inu Hardi; Solehudin, Agus (Universitas Pendidikan Indonesia, 2020)
his study aims to determine the effect of industrial work practice experience on readiness to enter the world of work of students with competency skills in Mechanical Engineering at SMK N 2 Bandung. The research was conducted at SMK N 2 Bandung with a research sample of 35 students of class XII TP 1 at SMK Negeri 2 Bandung. This type of research is survey research using a quantitative descriptive approach. The instrument used to collect data is manifested in the form of a questionnaire about work readinessand work practices. The data obtained were then converted into a Likert scale. This questionnaire consists of 39 items that have been tested for validation and reliability. The research data were analyzed using descriptive statistics with the help of SPSS22. The results of this study indicate that industrial work practices have a positive and significant effect on job readiness. This can be seen from the rxi value of 0.710, the coefficient of determination (r2xy) of 0.504 and tcount (5.790) t table (2.035). Based on the coefficient of determination (r2xy) 0.504, it means that 50.4% of students' work readiness is influenced by Industrial Work Practices, while the remaining 49.6% is influenced by other factors.